Surgical salvage via endoscopic assisted Lefort I osteotomy approach in recurrence nasopharyngeal carcinoma - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Kamarudin, Norie Azilah; Srinovianti , Noerdin (2005)
Objective; Surgical salvage for local recurrence in nasopharyngeal carcinoma has emerged as an important treatment option. The surgical approaches are divided into inferiorly by midline mandibulotomy or median labiomandibular glossotomy, laterally by facial translocation or transpterygoid approach and anteroposteriorly by maxillary swing or maxillectomy approach. Method; The purpose of this paper is to illustrate our surgical approach for nasopharyngectomy in two cases of recurrence nasopharyngeal carcinoma by means of endoscopic assisted Lefort I osteotomy. Results ; Both patients had achieved complete en-bloc resection of the tumor with the margins were free of the carcinoma. The morbidity of the surgical approach were minimal and the functional recovery after surgery were excellent. Conclusion; This surgical approach is a viable alternative for early stage in recurrence of nasopharyngeal carcinoma where the morbidity is minimal with excellent recovery.